Simultaneous Monitoring of Tyrosinase and ATP in Thick Brain Tissues Using a Single Two‐Photon Fluorescent Probe - Hong Huang; Huiru Li; Yong Zhang; Xuhan Xia; Ningwen Zhang; Haixin Fan; Longhua Guo; Yongyong Cao; Hu Pan; Ruijie Deng; Yangang Wang; Rodrigo Ledesma‐Amaro; et al. (Advanced Science)
Abstract Cellular redox homeostasis and energy metabolism in the central nervous system are associated with neurodegenerative diseases. However, their real‐time and concurrent monitoring in thick tissues remains challenging. Herein, a single dual‐emission two‐photon fluorescent probe (named DST) is designed for the simultaneous tracking of tyrosinase (TYR) and adenosine triphosphate (ATP), thereby enabling the real‐time monitoring of both neurocellular redox homeostasis and energy metabolism in brain tissue. The developed DST probe exhibits excellent sensitivity and selectivity toward TYR and ATP, with distinctive responses in the blue and red fluorescence channels being observed without spectra crosstalk. Using this probe, the correlation and regulatory mechanism between TYR and ATP during oxidative stress are uncovered. Additionally, the two‐photon nature of this probe allows alterations in the TYR and ATP levels to be monitored across different brain regions in an Alzheimer's disease (AD) mouse model. Notably, a significant decrease in ATP levels is revealed within the somatosensory cortex (S1BF) and caudate putamen brain regions of an AD mouse, alongside an increase in TYR levels within the S1BF and laterodorsal thalamic nucleus brain regions. These findings indicate the potential of applying the spatially resolved regulation of neurocellular redox homeostasis and energy metabolism to treat neurodegenerative diseases.